(untitled) (Global Journal of Human-Social Science, 2017)
In this article we study the relationship between the structure of the CEMAC banking market and financial stability Our results show that the concentration has a positive influence on the stability of the CEMAC banking market due to the presence of systemic banks belonging to the financial holding companies However this stability is threatened by the risk of illiquidity and the deterioration in the quality of the portfolios which depend to a large extent on the economic situation of the countries Therefore in the context of a macro prudential policy COBAC would benefit from establishing liquidity thresholds that should not be exceeded depending on the level of activity of each country in order to achieve a balance between efficiency and the stabilization of its banking system